Creating extra pores in microporous carbon via a template strategy for a remarkable enhancement of ambient-pressure CO2 uptake1. Issue 41 (21st May 2015) - Li, Baiyan; Zhang, Yiming; Ma, Dingxuan; Zhu, Liangkui; Zhang, Daliang; Chrzanowski, Matthew; Shi, Zhan; Ma, Shengqian
<x xml:space="preserve">Abstract</x> The creation of extra pores by removal of the silicon template in a porous carbon material derived from carbonizing silicon-containing POP has afforded a remarkable enhancement of ambient-pressure CO2 uptake capacity.